Implementing the flipped classroom methodology to the subject Applied computing of two engineering degrees at the University of Barcelona - Iborra Urios, Montserrat; Ramírez Rangel, Eliana; Badia Córcoles, Jordi Hug; Bringué Tomàs, Roger; Tejero Salvador, Javier (Journal of Technology and Science Education, 2017)
This work is focused on the implementation, development, documentation, analysis, and assessment of the flipped classroom methodology, by means of the just-in-time teaching strategy, for a pilot group (1 out of 6) in the subject “Applied Computing” of both the Chemical and Materials Engineering Undergraduate Degrees of the University of Barcelona. Results show that this technique promotes self-learning, autonomy, time management as well as an increase in the effectiveness of classroom hours